Effect of ticagrelor combined with metoprolol extended-release tablets on cardiac function and clinical prognosis in elderly patients with acute coronary syndrome after percutaneous coronary intervention - Lili Wang; Linlin Gao; Qin Chen; Li Chen; Hui Xu; Ling Sun; Youbin Hu (Frontiers in Cardiovascular Medicine)
BackgroundAcute coronary syndrome (ACS) poses significant risks to older individuals. This study sought to assess the impact of combining ticagrelor and metoprolol extended-release tablets on clinical prognosis and cardiac function in elderly ACS patients following percutaneous coronary intervention (PCI).MethodsFrom February 2022 to February 2023, 90 elderly ACS patients who underwent PCI at our institution were retrospectively enrolled and divided into two groups: an observation group (OG) and a control group (CG), with 45 patients in each group. The CG received oral metoprolol extended-release tablets, while the OG received both oral metoprolol extended-release tablets and ticagrelor. Prognostic indicators and cardiac function were evaluated before and after treatment.ResultsThe treatment effectiveness rate in the OG was 97.78%, significantly higher than the CG's rate of 77.78% (P < 0.05). Post-treatment, the OG displayed notable improvements in cardiac function, including significantly higher left ventricular ejection fraction (LVEF), stroke volume (SV), cardiac output (CO), and cardiac index (CI) compared to the CG (P < 0.05). Both groups experienced enhanced exercise capacity, as evidenced by longer exercise duration (ED) and improved 6-min walking test (6MWT) results, with the OG showing superior gains (P < 0.05). Additionally, the OG had significantly higher serum levels of cardiac troponin T (cTnT) and creatine kinase isoenzyme (CK-MB) than the CG (P < 0.05). Decreases in serum levels of sICAM-1, MMP-9, and hs-CRP were observed in both groups, with more pronounced improvements in the OG (P < 0.05). The incidence of adverse prognostic events in the OG was significantly lower at 8.89%, compared to 37.78% in the CG (P < 0.05).ConclusionTicagrelor combined with metoprolol extended-release tablets can significantly improve cardiac function, motor performance, and quality of life in ACS patients after PCI. Additionally, it effectively increases myocardial injury markers and reduces serum inflammatory factor levels.